2006
DOI: 10.1111/j.1750-3841.2006.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation on the Biological Activity of Green Tea Byproduct Extracts and a Comparison with Green Tea Leaf Extracts

Abstract: Green tea byproduct extract powder, a major byproduct of the green tea industry, was prepared and investigated for its biological activities after a gamma‐irradiation treatment for the purpose of a brightened color. The color, total phenolic contents, antioxidative activity, tyrosinase inhibition activity, cancer cell proliferation inhibition effect, and antimutagenicity were measured and compared with those of a green tea leaf extract powder. Hunter L* values of the irradiated green leaf and byproduct extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
5
9
2
Order By: Relevance
“…However, the effect of the irradiation technology on antioxidant capacity was reported for other plants and spices. Our finding was in agreement with that of Lee, Jo, Sohn, Kim, and Byun (2006), who reported the absence of a significant effect of gamma irradiation at 20 kGy on antioxidant capacity of green tea byproducts and green tea leaf extracts. Murcia et al (2004) also revealed that irradiation up to 10 kGy did not have any effect on the antioxidant capacities of seven dessert spices.…”
Section: Effect Of Gamma Irradiation On Antioxidant Capacity Of Olivesupporting
confidence: 94%
See 1 more Smart Citation
“…However, the effect of the irradiation technology on antioxidant capacity was reported for other plants and spices. Our finding was in agreement with that of Lee, Jo, Sohn, Kim, and Byun (2006), who reported the absence of a significant effect of gamma irradiation at 20 kGy on antioxidant capacity of green tea byproducts and green tea leaf extracts. Murcia et al (2004) also revealed that irradiation up to 10 kGy did not have any effect on the antioxidant capacities of seven dessert spices.…”
Section: Effect Of Gamma Irradiation On Antioxidant Capacity Of Olivesupporting
confidence: 94%
“…A similar observation was reported for green tea byproducts and green tea leaf extracts treated by gamma irradiation at dose of 20 kGy (Lee et al, 2006). However, gamma irradiation treatments have been shown to either increase or decrease the total phenolics content of plants materials, which is dependent on the dose delivered and the raw material used.…”
Section: Total Phenolics Contentsupporting
confidence: 81%
“…For extraction I, the 30 kGy sample still exhibited a higher total phenolic content than the nonirradiated control. Our results are in agreement with those of Lee and others (2006) who reported a decrease in phenolic content at higher irradiation doses (20 kGy) in green tea extracts but contrary to previous findings by Mishra and others (2006) who reported no change above 5 kGy. The decrease in total phenolic content suggests that phenolic compounds may be degraded or destroyed at the highest irradiation dose.…”
Section: Resultssupporting
confidence: 92%
“…However, no alteration in the distribution of phenolic acids was observed in irradiated cinnamon, cardamom, and mace possibly due to the presence of condensed tannins which have greater resistance to gamma radiation than hydrolysable tannins (Variyar and others 1998). Green tea extracts irradiated at 20 kGy had decreased phenolic content from the control sample in contrast to the aforementioned findings (Lee and others 2006). Mishra and others (2006) found that the total soluble phenolics were not altered in phenolic extracts of the boiled dry tea leaves after 5 kGy irradiation.…”
Section: Introductioncontrasting
confidence: 56%
“…L * -values significantly increased with the absorbed doses, but a * and b * -values decreased, which visually meant that the dark HCD colour turned brighter. There have been several reports on the increase of the Hunter colour L * -value in green tea extract (Jo, Son, Lee et al, 2003;Jo, Son, Shin et al, 2003) and green tea byproduct extracts (Lee, Jo, Sohn, Kim, & Byun, 2006) by gamma irradiation. Similar results in soybean sauce, Kanjang, have also been reported in other studies (Song, Kim, Park, Shin, & Byun, 2001).…”
Section: Colour Changesmentioning
confidence: 99%